A new genus and species of natricine snake from northeast India - Giri, Varad B.; Gower, David J.; Das, Abhijit; Lalremsanga, H.t.; Lalronunga, Samuel; Captain, Ashok; Deepak, V. (Zootaxa, 2019)
Based on the first molecular phylogenetic analyses of samples from northeast India, specimens referred to Rhabdops from this region are more closely related to the southeast and east Asian natricine genera Opisthotropis Günther, 1872 and Sinonatrix Rossman & Eberle, 1977 (as well as to New World and western Palearctic natricines) than to peninsular Indian (true) Rhabdops. Morphologically, these northeast Indian populations differ from other natricines by having a single (‘fused’ or unpaired) internasal shield and a single prefrontal shield. Given the morphological and phylogenetic distinctiveness of these northeast Indian populations, we refer them to a new genus, Smithophis gen. nov., and transfer Rhabdops bicolor (Blyth, 1854) to Smithophis bicolor comb. nov. Based on morphological and molecular variation within our northeast Indian sample, we additionally describe Smithophis atemporalis sp. nov. from the state of Mizoram.